Genetic Markers in the EET Metabolic Pathway Are Associated with Outcomes in Patients with Aneurysmal Subarachnoid Hemorrhage. Issue 2 (February 2015) - Donnelly, Mark K; Conley, Yvette P; Crago, Elizabeth A; Ren, Dianxu; Sherwood, Paula R; Balzer, Jeffery R; Poloyac, Samuel M
Preclinical studies show that epoxyeicosatrienoic acids (EETs) regulate cerebrovascular tone and protect against cerebral ischemia. We investigated the relationship between polymorphic genes involved in EET biosynthesis/metabolism, cytochrome P450 (CYP) eicosanoid levels, and outcomes in 363 patients with aneurysmal subarachnoid hemorrhage (aSAH). Epoxyeicosatrienoic acids and dihydroxyeicosatetraenoic acid (DHET) cerebrospinal fluid (CSF) levels, as well as acute outcomes defined by delayed cerebral ischemia (DCI) or clinical neurologic deterioration (CND), were assessed over 14 days. Long-term outcomes were defined by Modified Rankin Scale (MRS) at 3 and 12 months. CYP2C8∗4 allele carriers had 44% and 36% lower mean EET and DHET CSF levels ( P =0.003 and P =0.007) and were 2.2- and 2.5-fold more likely to develop DCI and CND ( P =0.039 and P =0.041), respectively. EPHX2 55Arg, CYP2J2∗7, CYP2C8∗1B, and CYP2C8 g.36785A allele carriers had lower EET and DHET CSF levels. CYP2C8 g.25369T and CYP2C8 g.36755A allele carriers had higher EET levels. Patients with CYP2C8∗2C and EPHX2 404del variants had worse long-term outcomes while those with EPHX2 287Gln, CYP2J2∗7, and CYP2C9 g.816G variants had favorable outcomes. Epoxyeicosatrienoic acid levels were associated with Fisher grade and unfavorable 3-month outcomes. Dihydroxyeicosatetraenoic acids were not associated with outcomes. No associations passed Bonferroni multiple testing correction. These are the first clinical data demonstrating the association between the EET biosynthesis/metabolic pathway and the pathophysiology of aSAH.